Small great things : a novel - Picoult, Jodi (Newyork: Allen & Unwin, 2016)
'If I cannot do great things, I can do small things in a great way.' Martin Luther King Jr..'I don't want that nurse touching my baby.' Those are the instructions from the newborn child's
Keywords: Fiction